NCOG-03. IMPACT OF THE RATE OF RADIOGRAPHIC RESPONSE (RR) OF BRAIN METASTASES (BM) TO WHOLE BRAIN RADIATION THERAPY (WBRT) ON NEUROCOGNITIVE FUNCTION (NCF) ON NRG-CC001. (14th November 2022) - Devisetty, Kiran; Pugh, Stephanie; Brown, Paul; Gondi, Vinai; Wefel, Jeffrey; Solanki, Abhishek; Kalapparambath, Tomy; Harmon, Grant; Saripalli, Anjali; Chou, Brian; Venkatesulu, Bhanu Prasad; Boike, Thomas; et al.
Abstract: BACKGROUND: The assessment of BM response to WBRT and its impact on NCF in clinical trials has been limited by lack of standardized imaging protocols. NRG-CC001 is a randomized clinical trial requiring pre-specified MRI protocols at baseline and 6-months, providing a uniform dataset to investigate if RR correlates with NCF changes. METHODS: NRG-CC001 randomized patients with BM to hippocampal avoidance WBRT (HA-WBRT) or WBRT. NCF was analyzed using 6-month standardized change scores and deterioration, defined using the reliable change index. Chi-square and t-tests were used for pretreatment characteristic comparisons. Inter-rater reliability between central and institutional assessment of RR was assessed with weighted kappa, κ. Linear regression was used to test trends in NCF change scores across types of response and multivariable logistic regression was used to test the association of RR to NCF deterioration. RESULTS: 149 and 135 patients were evaluable for RR and NCF assessment, respectively. Pretreatment characteristics were well-balanced, except for post-high school education (70.6% HA-WBRT vs. 52.5% WBRT, p=0.023). Inter-rater reliability between central and institutional assessment of RR was fair (κ=0.36). There was no difference between arms in RR (p=0.41) with overall rates of 14.1% CR, 42.2% PR, 17% SD, and 26.7% PD. Patients with CR had improved 6-month NCF change as measured by HVLT-R Total Recall (p=0.0005), HVLT-R Delayed Recall (p=0.0003), HVLT-R Delayed Recognition (p=0.011), TMT-B (p=0.033), COWA (p=0.016), and Clinical Trial Battery Composite score (p=0.0011). Multivariable analysis demonstrated less deterioration in HVLT-R Delayed Recall for CR (p=0.019) and PR (p=0.0086) vs. SD/PD and HVLT-R Recognition for PR (p=0.031) vs. SD/PD. CONCLUSIONS: HA-WBRT and WBRT result in similar RR at 6-months. CR or PR is associated with better NCF preservation. This suggests investigation into treatment escalation for patients with SD/PD may provide further NCF benefit along with HA-WBRT and memantine.Grant support from NCI-UG1CA189867 and U24CA180803.